The unexpected diva : a novel - Warren, Tiffany L. (William Morrow, an imprint of HarperCollins Publishers, 2025)
"Born into slavery on a Mississippi plantation, Elizabeth Taylor Greenfield has been raised in the safety of Philadelphia's Quaker community by a wealthy adoptive mother. Sheltered and educated, Eliza's happy childhood always included music lessons to nurture her unique gift: a glorious three octave singing voice that leaves listeners in awe. But on the eve of her twenty-fourth birthday, young Eliza's world is thrown into a tailspin when her mother dies. Eliza's inheritance is contested by her mother's white cousins, leaving her few options. She can marry her longtime beau, Lucien, though she has no desire to be a wife and mother. Or she can work as a tutor for rich families. Her mother's dying wish was for Eliza to pursue her talent and become a professional singer, but that grand vision now seems out of reach. When a chance performance on a steamboat to Buffalo, New York, leads to a surprising opportunity, fearless Eliza seizes her moment. Within a year she is touring America, singing to packed houses, and igniting controversy wherever she goes. In a country captivated by "the Swedish Nightingale" Jenny Lind, Eliza is billed by tour promoters as "the Black Swan." An unlikely diva, Eliza is tall, dark-skinned, and robust of figure compared to the petite European prima donna, but even the harshest critics can't deny Eliza's extraordinary gift. Menaced by racist crowds, threatened by slave-catchers who kidnap free Black people, Eliza lives a public life full of risk, but one which also holds the promise of great riches, and the freedoms those buy."--Back cover